(3QSGdI aj eOdhd GdfXe GdeYLRs - (3eMeO GdSYjO Hf eMjj GdOjf GdMSfj GdLRGFQj,J (B1278 (3g` s ((3YHO GdbGOQ Hf eMeO Hf jYbhH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO CjgG GdCHf GdcQje , habfi Gddg hEjGc dEJHGY GdefgL Gdbhje , Efc SCdJ efi QSGdI GNJUQ dc ajgG RHOi eGddCFeI GdCYdGe ai eOdhd GdfXe GdeYLR ef cdGe s
(3BNQgG (B:s
(3eG jcTa GdZWG Yf eKGQ GdTHgI ai eYfi GdcdGe , Ydi bOQ GdESJWGYI hGdLgO hgh JYGdi jfaY HGdfjI hGdbUO hGdMeO ddg ChdkG hBNQkG s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdHdGZIs